1994
DOI: 10.1002/mmce.4570040304
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric resonator antennas—a review and general design relations for resonant frequency and bandwidth

Abstract: Open dielectric resonators (DRs) offer attractive features as antenna elements. These include their small size, mechanical simplicity, high radiation efficiency due to no inherent conductor loss, relatively large bandwidth, simple coupling schemes to nearly all commonly used transmission lines, and the advantage of obtaining different radiation characteristics using different modes of the resonator. In this article, we give a comprehensive review of the modes and the radiation characteristics of DRs of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
478
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 790 publications
(495 citation statements)
references
References 36 publications
(56 reference statements)
10
478
0
Order By: Relevance
“…From Figure 4, it is confirmed that HEM 11δ and HEM 12δ modes are created inside the ring DRA at 3.0 GHz and 5.8 GHz, respectively [23]. This can also be confirmed by the following mathematical formulation [24]: …”
Section: Dual Band Generationsupporting
confidence: 58%
“…From Figure 4, it is confirmed that HEM 11δ and HEM 12δ modes are created inside the ring DRA at 3.0 GHz and 5.8 GHz, respectively [23]. This can also be confirmed by the following mathematical formulation [24]: …”
Section: Dual Band Generationsupporting
confidence: 58%
“…The measured S 11 offers the bandwidth of 76.7 %, ranging 4.5 GHz-10.1 GHz. The Radiation quality factor of DRA is inversely proportional to the bandwidth [11], …”
Section: Resultsmentioning
confidence: 99%
“…The DRA is an open resonating structure, fabricated from a low loss dielectric material. It offers advantages such as small size, high radiation efficiency due to the absence of conductor losses simple geometry, small size, flexible feed arrangement, wide range of material dielectric constant, ease of excitation and easily controlled characteristics As compared with microstrip antenna, the DRA has wider impedance bandwidth and better efficiency due to absence of surface wave [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bandwidth enhancement is becoming the major design consideration for most practical applications of dielectric resonator antennas [5]. The techniques used to improve the bandwidth of the DRAs include changing the aspect ratio of DRA, modifying feed geometries, employing multi-segments and stacked DRAs and by varying the dielectric constant of DRA material [6,7].…”
Section: Introductionmentioning
confidence: 99%